Post COVID rhino-cerebral mucormycosis at a tertiary hospital in Central India: a retrospective cohort study - Sagar Shankarrao Gaurkar; Prasad Trimbakrao Deshmukh; Farhat Qamruddin Khan (The Egyptian Journal of Otolaryngology)
Abstract Background Usually non-pathogenic in immunocompetent individuals, mucormycosis is an aggressive, angio-invasive fungus. It is a rare, opportunistic infection belonging to the zygomycete family. The second wave of COVID-19 saw the emergence of a more dangerous and a potentially deadly invasive fungal sinusitis evolving in rhino-cerebral mucormycosis thus compounding and complicating the pandemic. Alarming and exponential rise in the number of cases of rhino-cerebral mucormycosis in India versus the rest of the world when the treatment protocols essentially remained the same needs to be probed scientifically along with its prompt management. Here an attempt has been made to explore this in the study of 50 cases of rhino-cerebral mucormycosis. This study aims to explore the cause and extension of the disease along with its treatment and outcome in 50 cases of post COVID rhino-cerebral mucormycosis. Results This is a retrospective cohort study conducted on 50 patients with post COVID-19 invasive mucormycosis of the paranasal sinuses with extension to surrounding structure visiting Otorhinolaryngology department at Acharya Vinoba Bhave Rural Hospital, Wardha. Among 50 patients, 86% males in 4th to 7th decade with mean age of 51.08 years. Large majority had mild–moderate severity on high-resolution computed tomography thorax with 84% having uncontrolled diabetes and 18% newly diagnosed diabetic cases. Seventy-two percent had history of steroid intake for COVID-19 management. Maxillary sinus was most commonly involved sinus in 94% cases while 32% had commonest extra nasal spread hard palate. Seventy-eight percent of the post operated mucormycosis cases are alive with no recurrence, 8% are alive and had recurrence of the disease while 14% resulted in death. Conclusion Effective management and control of the infection can be achieved with the use of strong antibiotics, oral or systemic antifungal drugs, extensive surgical excision of diseased tissue, and addressing underlying risk factors can effectively manage and control the infection. This approach results in positive outcomes and reduced morbidity compared to the time prior to the COVID-19 pandemic including cases with extensive disease.